Comparison of the 3D-Microstructure Between Alveolar and Iliac Bone for Enhanced Bioinspired Bone Graft Substitutes - Rothweiler, Rene; Gross, Christian; Bortel, Emely; Früh, Sarah; Gerber, Javier; Boller, Elodie; Wüster, Jonas; Stricker, Andres; Fretwurst, Tobias; Iglhaut, Gerhard; Nahles, Susanne; Schmelzeisen, Rainer; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
In oral- and maxillofacial bone augmentation surgery, non-vascularized grafts from the iliac crest demonstrate better clinical performance than alveolar bone grafts. The underlying mechanisms are not fully understood but are essential for the enhancement of bone regeneration scaffolds. Synchrotron Radiation µ-CT at a pixel size of 2.3 μm was used to characterize the gross morphology and the vascular and osteocyte lacuna porosity of patient-matched iliac crest/alveolar bone samples. The results suggest a difference in the spatial distribution of the vascular pore system. Fluid simulations reveal the permeability tensor to be more homogeneous in the iliac crest, indicating a more unidirectional fluid flow in alveolar bone. The average distance between bone mineral and the closest vessel pore boundary was found to be higher in alveolar bone. At the same time, osteocyte lacunae density is higher in alveolar bone, potentially compensating for the longer average distance between the bone mineral and vessel pores. The present study comprehensively quantified and compared the 3D microarchitecture of intraindividual human alveolar and iliac bone. The identified difference in pore network architecture may allow a bone graft from the iliac crest to exhibit higher regeneration potential due to an increased capacity to connect with the surrounding pore network of the residual bone. The results may contribute to understanding the difference in clinical performance when used as bone grafts and are essential for optimization of future scaffold materials.